Answer:
h(4) = –12
Step-by-step explanation:
⇒ What the question is asking is that when the function h(n) = –2n(2) + 4 is h(4), what will the function repond to when solving for h(4)? So, solve for the function h(4):
h(4) = –2n(2) + 4
⇒ Since n was replaced with 4 in the function h(4), substitute any n for 4 into the function:
h(4) = –2(4)(2) + 4
⇒ Simplify:
h(4) = –16 + 4
⇒ Solve:
h(4) = –12
<u>Answer:</u> h(4) = –12
<em>I hope you understand and that this helps with your question! </em>:)
Answer:
-12
Step-by-step explanation:
Answer:
21
Step-by-step explanation:
put 21 were x is and then divide 21÷7=3
Step-by-step explanation:
The slope of the line is -4/7.
Answer:
He is right he can eat 2/6 f the whole pan of lasagna
Step-by-step explanation:
We had 2/3 pan of lasagna and pads family ate 1/2 of it, then
padis family ate (2/3) /2 or 2/6
2/6 is half of the total pan of lasagna, padis family ate half of 2/3 wich is 2/6 and left 2/6 for Felix